Efferent Vision Therapy. Issue 2 (June 2018) - Rucker, Janet C.; Phillips, Paul H.
Abstract : Background: Traditional orthoptic therapy used by ophthalmologists, orthoptists, and optometrists is directed at improving visual acuity, ocular alignment, or both. For example, convergence exercises are used to treat convergence insufficiency (CI). However, other forms of "vision therapy" are directed at improving "visual processing and efficiency." The therapeutic regimen often entails repetitive ocular motor tasks performed during multiple office visits with a behavioral optometrist. These ocular motor tasks are used to treat diverse conditions such as learning disabilities, poor reading ability, dyslexia, and attention-deficit hyperactivity disorder (ADHD). Evidence regarding the efficacy of therapy directed at ocular motility for the treatment of multiple conditions is reviewed. Evidence Acquisition: Review of literature. Results: Randomized, controlled, double-masked studies show that convergence exercises reduce symptoms and improve signs of CI in otherwise healthy patients. However, the most efficacious convergence tasks, and the optimal duration and frequency of these tasks, remain unknown. Patients with learning disabilities, poor reading ability, dyslexia, or ADHD do not consistently have unique ocular motor deficits. Patients who acquire ocular motor deficits do not develop these conditions. There are no randomized, controlled studies that show treatment consisting of repetitive ocular motor tasks improves learning disabilities, reading, dyslexia, or ADHD. Conclusions: Convergence exercises effectively treat CI in healthy patients. The optimal treatment regimen is unknown. There is insufficient evidence to recommend "vision therapy" for the treatment of learning disabilities, impaired reading, dyslexia, or ADHD.